Dopamine replacement remediates risk aversion in Parkinson's disease in a value-independent manner. (September 2019) - Cherkasova, Mariya V.; Corrow, Jeffrey C.; Taylor, Alisdair; Yeung, Shanna C.; Stubbs, Jacob L.; McKeown, Martin J.; Appel-Cresswell, Silke; Stoessl, A. Jon; Barton, Jason J.S.
Abstract: Introduction: Clinical evidence suggests that Parkinson's Disease (PD) patients are risk averse. Dopaminergic therapy has been reported to increase risk tolerance, but the underlying mechanisms are unclear. Some studies have suggested an amplification of subjective reward value, consistent with the role of dopamine in reward value coding. Others have reported value-independent risk enhancement. We evaluated the value-dependence of the effects of PD and its therapy on risk using tasks designed to sensitively measure risk over a wide range of expected values. Method: 36 patients with idiopathic PD receiving levodopa monotherapy and 36 healthy matched controls performed two behavioural economic tasks aimed at quantifying 1) risk tolerance/aversion in the gain frame and 2) valuation of potential gains relative to losses. PD patients performed the tasks on and off their usual dose of levodopa in randomized order; controls performed the same tasks twice. Results: Relative to the controls, unmedicated PD patients showed significant value-independent risk aversion in the gain frame, which was normalized by levodopa. PD patients did not differ from controls in their valuation of gains relative to losses. However, across both tasks and regardless of medication, choices of the patients were more determined by expected values of the prospects than those of controls. Conclusion: Dopamine deficiency in PD was associated with risk aversion, and levodopa promoted riskier choice in a value-independent manner. PD patients also showed an increased sensitivity to expected value, which was independent of levodopa and does not appear to result directly from dopamine deficiency. Highlights: Unmedicated PD patients were risk-averse for gains regardless of their expected value. This risk aversion was normalized by levodopa. PD patients did not differ from controls in their valuation of gains relative to losses in either the OFF or the ON state. Choices of PD patients in both OFF and ON states were more driven by expected value than those of controls.